Experimental Investigation on Effects of Elastic Agitator to Turbulence Enhancement - Yong, T.H. (Isfahan University of Technology, 2020)
The conventional method to promote mass, momentum and energy transport between fluid particles is to introduce a disturbance to the flow. An ultrasonic velocity profiler, UVP experiment was used to study the mean and fluctuating flow properties in the near wake of the rigid and flexible protruding surface in a water tunnel under the Reynolds number of 4000, 6000 and 8000. In the current study, circular finite cylinders (cantilevers) with various aspect ratios (AR = 10, 12, 14 and 16) and materials were used as the geometry of the rigid and protruding surface. The motion of the cylinder alters the fluid flow significantly. The increment of the wake region (~10 larger in the flexible cylinder compared to the rigid case, for AR = 16) is due to the weakening of the influence of downwash caused by the stream-wise deflection of the flexible cylinder. As a mean to quantify turbulence, the turbulent intensity, Ti, was studied. In general, the flexible cylinders show better capability in augmenting the turbulence than the rigid cylinder. The stream-wise turbulent intensity for AR = 16 and Re = 8000 can be as high as 97 for the flexible cylinder compared to only 26 for the rigid case. The normalized amplitude response graph, which records the cross-flow oscillation of the flexible cylinder was also analyzed. Under the same Reynolds number, the turbulence enhancement increases with the structural velocity. An organized oscillating motion is in favor of a higher performance of turbulence enhancement. Â© 2020 All Rights Reserved